Ionomic and Metabolomic Analyses Reveal Different Response Mechanisms to Saline–Alkali Stress Between Suaeda salsa Community and Puccinellia tenuiflora Community - Chen, Qi; Jin, Yan; Zhang, Zhonghua; Cao, Meng; Wei, Guanyun; Guo, Xiaorui; Zhang, Jian; Lu, Xueyan; Tang, Zhonghua (Frontiers in Plant Science, 2021)
Soil salinization imposes severe stress to plants, inhibits plant growth, and severely limits agricultural productivity and land utilization. The response of a single plant to saline-alkali stress has been well investigated. However, plant community usually works as a group to defend against saline-alkali stress, were neglected. To determine the functions of plant community, in our current study, Suaeda salsa (S. salsa) community and Puccinellia tenuiflora (P. tenuiflora) community, two communities that are widely distributed in Hulun Buir Grassland in Northeastern China, were selected as research objects. Ionomic and metabolomic were applied to compare the differences between S. salsa community and P. tenuiflora community from the aspects of ion transport and phenolic compound accumulation, respectively. Ionomic studies demonstrated that many macroelements, including potassium (K) and calcium (Ca), were highly accumulated in S. salsa community while microelement manganese (Mn) was highly accumulated in P. tenuiflora community. In S. salsa community, transportation of K to aboveground parts of plants helps to maintain high K+ and low Na+ concentrations while accumulation of Ca triggers the salt overly sensitive (SOS)-Na+ system to efflux Na+. In P. tenuiflora community, enrichment of Mn in roots elevates the level of Mn-superoxide dismutase (SOD) and increases the resistance to saline-alkali stress. Metabolomic studies revealed the high levels of C6C1-compounds and C6C3C6-compounds in S. salsa community as well as the high levels of C6C3-compounds in P. tenuiflora community. C6C1-compounds function as signaling molecules to defend against stress and may stimulate the accumulation of C6C3C6-compounds. C6C3-compounds contribute to the elimination of free radicals and the maintenance of cell morphology. Collectively, our findings determine the abundances of various elements and phenolic compounds in S. salsa community and P. tenuiflora community in Hulun Buir Grassland, explore different responses of S. salsa community and P. tenuiflora community to cope with saline-alkali stress. Understanding of plant response strategies from the perspective of community teamwork, and thus may provide a feasible and novel way to transform salinization land.